The pelleting of micro-fine agricultural lime to treat soil acidity, using sodium alginate, lignosulphonate, and bentonite as binders - Schwaeble, Claudia Francesca (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.